KETERLIBATAN MASYARAKAT DALAM MENGELOLA DESA WISATA PANGSAN DI KABUPATEN BADUNG - Eka Maharini, Dewa Ayu; Arida, I Nyoman Sukma (JURNAL DESTINASI PARIWISATA; Vol 2 No 1 (2014): VOL 2, NO 1 (2014): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2014)
ABSTRACT The purpose of this study was to determine the potential Pangsan Tourism Village as a tourist village in Badung regency and to know the community involvement in managing Pangsan Tourism Village. The target of this research is Pangsan Tourism Village and the manager is involved in managing Pangsan Tourism Village. Collecting data in this study, by observation, in-depth interviews, and literature study. Determination technique using purposive informan sampling is subjective determination based on the study with certain considerations. Analysis data in this study is descriptive qualitative. Based on this research, there is an overview of the potential of the Pangsan Tourism Village in the form of potential physical and non-physical. Physical potential offers several activities that can be enjoyed by tourists as trekking, rafting and cycling. In addition it also obtained data on community involvement in managing Pangsan Tourism Village and management aspects of the organization include: organizational structure, history institutions and legality, interaction with others and sharing system. Marketing aspects include: promotion, price and tourist arrivals. Aspects of human resources include: system / division of labor and education and training.
Keywords: Keywords : potential , management and community involvement.